The use of saliva and blood progesterone to profile the menstrual cycles of youth professional football players - Ferrer, Eva; Rodas, Gil; Casals, Gregori; Trilla, Antoni; Balagué-Dobon, Laura; González, Juan R.; Ridley, Katherine; White, Richard; Burden, Richard J. (Frontiers in Sports and Active Living, 2024)
Background Understanding individual ovarian hormone cycles and their relationship with health, performance and injuries is highly important to practitioners supporting female athletes. Venous blood sampling is the current gold standard for measuring the ovarian hormones, but the invasive nature of this method presents a major barrier in sport environments. Saliva analysis may offer an alternative method as it is non-invasive, allowing the sample to be collected “in situ”, with relative ease, necessary in applied sport environments. Objective The aims of this study were: (i) To compare the concentration of progesterone between capillary blood and saliva, (ii) To assess the efficacy of weekly measurements of progesterone for determining if ovulation has occurred in elite eumenorrheic football players, and (iii) To establish a saliva criteria cut-off for establishing ovulation and assessing the sensitivity, specificity and accuracy values of the method. Methodology Twenty-one professional and semi-professional, Spanish league female football players (18.6 ± 1.5 years, 58.1 ± 6.0 kg, 164.0 ± 4.8 cm) with natural menstrual cycles, completed the study. Capillary blood and saliva samples were collected from each participant on twelve occasions each separated by at least 7 days. All samples were collected in the morning, following an overnight fast. Results According to luteal phase serum progesterone concentrations, 11 out of 21 (52%) players presented with menstrual irregularities (oligomenorrheic n = 6, anovulatory n = 4, amenorrhoeic n = 1). A significant correlation was observed between plasma and saliva progesterone in the estimated eumenorrheic group (r = 0.80, p = <0.001, 95% CI 0.72–0.86). The association between serum and saliva progesterone was weaker in the oligomenorrheic group (r = 0.47, p = <0.001, 95% CI 0.27–0.64) and was not present in the anovulatory or amenorrhoeic groups. Conclusions Salivary measurements of progesterone are well correlated with capillary blood when taken during eumenorrheic menstrual cycles and presents a viable, non-invasive method of establishing characteristic progesterone fluctuations in applied sport settings. The strength of the association appears to be concentration dependent. A luteal phase saliva progesterone (P4) >50 pg/ml and >1.5× follicular baseline has good sensitivity, specificity, and accuracy to indicate ovulation compared to established criteria for serum progesterone.